Buku Cerita Si Kancil dan Perilaku Meniru Siswa Taman Kanak-kanak - Syukria Syukria; Nina Siti Salmaniah Siregar (Universitas Negeri Medan, 2018)
The purpose of this paper is to find out whether the storybook or the Kancil fairy tale influences the imitating behavior of the Sunggal 41 ABA 41 Kindergarten students and sees how storytellers are very influential in conveying the message content of a story. This research method uses descriptive, which is taking a problem or focusing on actual problems as they were at the time the research was conducted. The description in this study was to see the imitating behavior of the Sunggal 41 ABA Kindergarten students. The results of the study found that fairy tales or stories of the Kancil can enrich knowledge by recognizing various types of animals that are used as characters in a story or fairy tale or in increasing children's understanding of good and bad things. Children who tend to not be able to focus on one thing / object in a certain period of time are challenges and homework that the teacher must overcome when telling stories / storytelling. Short time and schedule of storytelling / storytelling activities obtained at school are not enough to-create-imitating-behaviors-of-children.